Leaf-feeding species of the genus Liothrips from China (Thysanoptera, Phlaeothripinae) - Dang, Lihong; An, Yiyan; Mound, Laurence A.; Qiao, Gexia (Zootaxa, 2024)
The 250 species of the second largest genus of Thysanoptera, Liothrips, are known as feeding mainly on green leaves, with many inducing galls or associated with galls. In China, 33 species are recognized including L. brevis sp. n., L. elongatus sp. n., L. longistylus sp. n., L. motuoensis sp. n., L. piceae sp. n., L. populi sp. n. and L. tibetanus sp. n., also seven species are recorded from this country for the first time. Four Han’s Liothrips species are considered as new synonymies of L. vaneeckei that might be widespread in the Holarctic region. Three species are newly combined as Liothrips aporosae comb.n., Teuchothrips fuscus comb.n. and T. turkestanicus comb.n. The illustrated identification key to Chinese Liothrips species excludes L. hsuae but includes L. mirabilis due to its potential as a pest of Piper plants are growing throughout Southern China. Biology, structural variation, and generic relationships are also discussed.